PROBING THE CHALLENGES EXPERIENCED BY PERFORMERS OF CULTURE AND THE ARTS - Tabao, Kristel Joy (International Journal of Arts, Sciences and Education, 2022)
It is necessary to have an educated grasp of this culture and to actively participate with it in some way, whether formally or informally, if one wants to have a holistic perspective on life and to have respect for what is all around us. This study's overarching objective was to investigate the difficulties that members of Cagayan State University's Culture and Arts club face on a day-to-day basis. Quantitative research was utilized to acquire information dealing with the statistical information in order to identify whether or not dependent variables pertaining to the personal profile were significant factors influencing the difficulties that student performers were required to overcome. The findings showed that teachers acknowledged the performers' dual roles as students and performers; coaching staff valued and understood the importance of prioritizing both academics and performing arts; and respondents were frequently given access to a nutritious meal during rehearsals and competitions, in addition to a medical team that assisted in monitoring their current health concerns and provided them with any necessary prescriptions or vitamins. The facts demonstrated that the presumptions that were made about their intellectual capacities and attributes were erroneous, and the struggle that they faced was in their academics.